Mixed ductal‐lobular carcinomas: evidence for progression from ductal to lobular morphology. Issue 4 (9th March 2018) - McCart Reed, Amy E; Kutasovic, Jamie R; Nones, Katia; Saunus, Jodi M; Da Silva, Leonard; Newell, Felicity; Kazakoff, Stephen; Melville, Lewis; Jayanthan, Janani; Vargas, Ana Cristina; Reid, Lynne E; Beesley, Jonathan; et al.
Abstract: Mixed ductal–lobular carcinomas (MDLs) show both ductal and lobular morphology, and constitute an archetypal example of intratumoural morphological heterogeneity. The mechanisms underlying the coexistence of these different morphological entities are poorly understood, although theories include that these components either represent 'collision' of independent tumours or evolve from a common ancestor. We performed comprehensive clinicopathological analysis of a cohort of 82 MDLs, and found that: (1) MDLs more frequently coexist with ductal carcinoma in situ (DCIS) than with lobular carcinoma in situ (LCIS); (2) the E‐cadherin–catenin complex was normal in the ductal component in 77.6% of tumours; and (3) in the lobular component, E‐cadherin was almost always aberrantly located in the cytoplasm, in contrast to invasive lobular carcinoma (ILC), where E‐cadherin is typically absent. Comparative genomic hybridization and multiregion whole exome sequencing of four representative cases revealed that all morphologically distinct components within an individual case were clonally related. The mutations identified varied between cases; those associated with a common clonal ancestry included BRCA2, TBX3, and TP53, whereas those associated with clonal divergence included CDH1 and ESR1 . Together, these data support a model in which separate morphological components of MDLs arise from a common ancestor, and lobular morphology can arise via a ductal pathway of tumour progression. In MDLs that present with LCIS and DCIS, the clonal divergence probably occurs early, and is frequently associated with complete loss of E‐cadherin expression, as in ILC, whereas, in the majority of MDLs, which present with DCIS but not LCIS, direct clonal divergence from the ductal to the lobular phenotype occurs late in tumour evolution, and is associated with aberrant expression of E‐cadherin. The mechanisms driving the phenotypic change may involve E‐cadherin–catenin complex deregulation, but are yet to be fully elucidated, as there is significant intertumoural heterogeneity, and each case may have a unique molecular mechanism. © 2018 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.